Konsep Li’an dalam Al-Qur’an (Studi Komparatif Tafsīr Al-Munīr dan Tafsīr al-Qurṭubī) - Zidan Telaumbanua; Alwin Tanjung; Aulya Adhli (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study examines the concept of li'an in the Qur'an through a comparative study between Wahbah Az-Zuhaili's Tafsīr Al-Munīr and Abu ‘Abdullah Al-Qurṭubī's Tafsīr al-Qurṭubī. Li'an is an Islamic legal mechanism used to resolve accusations of adultery by a husband against his wife without the presence of four witnesses, as stipulated in Surah An-Nur verses 6-9. This study is motivated by the importance of protecting honor and justice in Muslim families, as well as the need for sharia solutions when sensitive and difficult to prove internal domestic conflicts occur. This study uses a qualitative method with a library study approach and comparative analysis. Data were collected through a review of primary and secondary literature, particularly the two major tafsir books that are the objects of the study. The analysis focuses on the interpretive methodology of both commentators, the substance of their explanations of li'an, and the differences and similarities in interpreting related verses. The results show that Tafsīr Al-Munīr and Tafsīr al-Qurṭubī both emphasize li'an as a sharia solution that prioritizes justice and maintains the honor of both parties in the household. Both highlight the importance of mutual curses as a substitute for testimony in cases of adultery accusations without witnesses, and emphasize the legal consequences of dissolution of marital relations and child lineage. However, there are differences in the emphasis on legal and social aspects: Tafsīr Al-Munīr emphasizes the dimensions of benefit and family protection, while Tafsīr al-Qurṭubī delves more deeply into the fiqh and historical aspects of li'an implementation in classical times.